Association of Lean Body Mass and Fat Mass With 1-Year Mortality Among Patients With Heart Failure - Ge, Yilan; Liu, Jiamin; Zhang, Lihua; Gao, Yan; Wang, Bin; Wang, Xiuling; Li, Jing; Zheng, Xin (Frontiers in Cardiovascular Medicine, 2022)
Background Prior studies have found an unexplained inverse or U-shaped relationship between body mass index (BMI) and mortality in heart failure (HF) patients. However, little is known about the independent effects of each body component, i.e., lean body mass (LBM) and fat mass (FM), on mortality. Methods We used data from the China Patient-centered Evaluative Assessment of Cardiac Events-Prospective Heart Failure Study. LBM and FM were calculated using equations developed from the National Health and Nutrition Examination Survey. LBM and FM index, calculated by dividing LBM or FM in kilograms by the square of height in meters, were used for analysis. We used restricted cubic spline and Cox model to examine the association of LBM and FM index with 1-year all-cause mortality. Results Among 4,305 patients, median (interquartile range) age was 67 (57–76) years, 37.7% were women. During the 1-year follow-up, 691 (16.1%) patients died. After adjustments, LBM index was inversely associated with mortality in a linear way (P-overall association < 0.01; P-non-linearity = 0.52), but no association between FM index and mortality was observed (P-overall association = 0.19). Compared with patients in the 1st quartile of the LBM index, those in the 2nd, 3rd, and 4th quartiles had lower risk of death, with hazard ratio of 0.80 (95% CI 0.66–0.97), 0.65 (95% CI 0.52–0.83), and 0.61 (95% CI 0.45–0.82), respectively. In contrast, this association was not observed between FM index quartiles and mortality. Conclusion Higher LBM, not FM, was associated with lower 1-year mortality among HF patients.